(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Precise three-dimensional assessment of the mandibular canal is essential before posterior mandibular implant placement because variations in canal course, terminal branching, and proximity to the alveolar crest may increase the risk of inferior alveolar nerve injury. Methods This cross-sectional cone-beam computed tomography (CBCT) study evaluated 240 mandibular scans of adults aged 20-70 years. Bilateral measurements were made at the second premolar, first molar, and second molar regions. Canal-to-crest distance, canalto- buccal cortex distance, canal diameter, anterior loop length, bifid canal prevalence, and implant-related risk zones were recorded. Interobserver reliability was assessed using intraclass correlation coefficients. Results The mean age was 42.8 ± 12.6 years, with 126 males (52.5%) and 114 females (47.5%). Mean canal-to-crest distance reduced posteriorly from 17.64 ± 2.92 mm at the second premolar to 13.21 ± 2.76 mm at the second molar (p<0.001). The mandibular canal was positioned significantly closer to the buccal cortex in the second molar region (4.18 ± 1.06 mm) than in the premolar region (5.62 ± 1.21 mm; p<0.001). An anterior loop was detected in 34.6% of patients, with a mean length of 2.36 ± 0.91 mm. Bifid mandibular canal was observed in 14.2% of patients, most commonly the retromolar type. High-risk implant zones, defined as canal-to-crest distance <10 mm or anterior loop >3 mm, were identified in 19.6% of scans. Conclusion CBCT demonstrated clinically relevant mandibular canal variations that may alter implant length, angulation, and safety margins. Routine preoperative CBCT interpretation should include systematic mapping of the canal, anterior loop, and accessory branches before implant surgery. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S290-S296